A healthy active city : an urban planning perspective :Powerpoint - Zandieh, R. (University of Twente, 2020)
This lecture presents: Urban Planning; Health problems in cities; Physical activity guidelines; Inactivity in citizens; Increasing level of physical activity; Factors; Location.